PENGARUH STRUKTUR MODAL, PROFITABILITAS, PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia tahun 2011-2013) (Students' Journal of Accounting and Banking, 2015)
This research test the influence of capital structure, profitability, the company growth on the value companies. The research doing in Indonesian stock exchange for 3 years using analysis unit manufacturing company. The method sampling using a purposive sampling by period of 2011 to 2013. The analysis technique that use disregression ordinary least squares (OLS). As a condition for statistical testing has been done normality test and classical assumption that the results show that data distribution is the norm and escaped from the classical assumption. The results of this research suggests that capital structure is positive influence and no significant on the value companies . Profitability and significant effect on firm value.The latest results show that the growth of companies have negative effects and no significant impact on the company.Keywords: Firm Value, Capital Structure, Probability, Growth